Everyday Hair Discourses of African Black Women - Majali, Zukiswa; Coetzee, Jan K.; Rau, Asta (Qualitative Sociology Review, 2017)
Hair for African Black people has always had meaning. In the past, elaborate hairstyles communicated their status, identity, and place within the larger society. In present day society, hair continues to be a significant part of being an African Black person. Especially for women, who attach a number of different meanings to hair. This study casts more light on young African Black women’s everyday perceptions of hair and uncovers the meanings they attach to hair and beauty. This is done by looking at how the intersections of race, gender, and class impact on their everyday perceptions and experiences of hair. The literature indicates that the hair preferences and choices of Black African women tend to emulate Western notions of beauty. This is due to a great extent to the historical link between Black hair and “bad” hair associated with old slave days. But, the narratives of participants contradict this normative discourse in many ways and provide new insights on hair — insights that reflect and motivate antiracist aesthetics.